Dinâmica do metabolismo micromolecular da cana-de-açúcar em resposta à infecção com o fungo Puccinia kuehnii (ferrugem alaranjada) - Coutinho, Isabel Duarte [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Sugarcane is the main agricultural crop in economic importance of tropical regions and Brazil has the largest cultivation acreage in the world. The modern varieties are arising mainly from the crossing of Saccharum officinarum X Saccharum spontaneum. With the technological development of breeding programs, many old diseases affecting sugarcane were overcome through the development of resistant genotypes. However, in 2009 the first appeareance of orange rust in São Paulo State led to huge economic loss, because varieties with characteristics of high yield and resistance to brown rust were susceptible to orange rust. Therefore, this study aimed the micromolecular characterization of the sugarcane genotypes resistant and susceptible to orange rust by employing LC-DAD-MS and 1H NMR as well as analysis of both genotype extracts by HPLC-DAD and multivariate analysis. For the characterization step, the extract prepared from 500 mg of sugarcane leaves employing H2O/MeOH (8:2) was fractioned in 60 fractions and analyzed by LC-DAD-MS and 1H NMR. This step allowed the identification of 52 metabolites, including amino acids, sugars, organic acids, such as benzoic and phenolic, and flavones, out of which 33 are described for the first time in sugarcane. On the second step, the genotypes IAC95 5000 (resistant) and SP89 1115 (susceptible) growing under control conditions and inoculated with Puccinia kuehnii were analyzed by HPLC-DAD e submitted to multivariate analysis by PCA. In the first experimental design, the seedlings of IAC95 5000 and SP89 1115 genotypes with 30 days were maintained in growth room at 25 ºC. The harvest was carried out on 30, 35, 40, 45 and 60 day old seedlings at 6 am and 8 pm. The PCA of this experiment showed that the resistant genotype has the highest correlation of with luteolin derivatives. In the second experimental design, 25 plants were inoculated and 25 were considered as control for each genotype. The seedlings were...

A cana-de-açúcar é a principal cultura agrícola em importância econômica das regiões tropicais, sendo que o Brasil possui a maior área cultivada e em expansão do mundo. As variedades modernas são oriundas principalmente do cruzamento entre Saccharum officinarum e Saccharum spontaneum. Com o desenvolvimento tecnológico dos programas de melhoramento genético, muitas doenças antigas da cana-de-açúcar foram superadas através do desenvolvimento de genótipos resistente. Entretanto, no ano de 2009 o aparecimento da ferrugem alaranjada no estado de São Paulo causou grande prejuízo econômico, porque variedades com características de alta produtividade e resistência à ferrugem marrom, mostraram-se suscetíveis à ferrugem alaranjada. Diante disso, este trabalho teve por objetivo a caracterização micromolecular de genótipos de cana-de-açúcar resistentes e suscetíveis à ferrugem alaranjada, visando à identificação de marcadores moleculares de resistência a esse patógeno. Para isso, empregaram-se LC-DAD-MS e 1H NMR para obtenção de dados analíticos e métodos quimiométricos para análise multivariada. Para a etapa de caracterização, o extrato hidro-alcoólico preparado a partir de 500 mg das folhas de cana-de-açúcar foi fracionado em HPLC-DAD, fornecendo 60 frações que foram analisadas por LC-DAD-MS e 1H NMR. Esta etapa permitiu a identificação de 52 metabólitos, entre aminoácidos, açúcares, derivados do ácido benzoico, ácido hidroxicinâmico e flavonas C e O glicosiladas. Na segunda etapa foram avaliados os fingerprintings metabólicos dos genótipos resistentes (IAC95 5000) e suscetíveis (SP89 1115) empregando LC-DAD e submetidos a PCA. No primeiro planejamento experimental as mudas de ambos os genótipos com 30 dias foram transferidas para câmara de crescimento e mantidas a 25 ºC durante 30 dias. A PCA deste experimento mostrou que o genótipo resistente possui maior correlação com derivados de...
Keywords: Cana-de-açúcar; Metabolômica; Cromatografia líquida de alta eficiência; Sugarcane